Knowledge and Utilization of Family Planning among Reproductive Age Women in a Community of Banke - Mahato, Renu Kumari; Acharya, Sunita (Academia Research Journal, 2026)
Family planning plays important role in the growth and development reproductive health of reproductive age women. Maternal mortality is associated with the unmet need of family planning. Proper utilization of family planning is the best interventions to reduced maternal and neonatal morbidity and mortality. This study aims to assess the level of knowledge and utilization of family planning among Reproductive age women in a community of Banke. A descriptive cross -sectional study was conducted at Nepalgunj-19, Banke among 67 reproductive age women by using Non-probability, Purposive sampling technique and semi-structured questionnaire was used to collect data. The collected data was entered in SPSS version 16 and analysed by using descriptive statistics (such as frequency, percent, median, interquartile range, mean and standard deviation). This study revealed that, more than half (59.7%) of respondents had good level of knowledge, where less than half (40.3%) of respondents had poor level of knowledge regarding Family Planning and more than half (58.2%) of respondents had currently used different type of short-term or long-term family planning, among them more than one quarterly (30.7%) of respondents had used Depo-Provera as short-term family planning method and only (12.8%) had used implant as a long-term family planning method. The study finding reveals that more than half of respondents had good knowledge on family planning. Most of the respondents knew about only one method of family planning. Majority of the respondents had incomplete information regarding short-term and long-term family planning method. So that there is need to increase information regarding family planning through the preferred community channels.